An Ordinance Prohibiting the Carrying of Firearms, Ordinances of the Corporation of Georgetown (1859) - (:unkn) unknown (My University, 1859)
It shall not be lawful for any person or persons to have about their persons any concealed deadly or dangerous weapons, such as daggers, pistols, bowie-knives, dirk-knives, colt, slung-shots, or brass or other metallic knuckles, within the limits of this Corporation.
Keywords: CARRY